The role of the lymphatic system in cholesterol transport - Huang, Li-Hao; Elvington, Andrew; Randolph, Gwendalyn J. (Frontiers in Pharmacology, 2015)
Reverse cholesterol transport (RCT) is the pathway for removal of peripheral tissue cholesterol and involves transport of cholesterol back to liver for excretion, starting from cellular cholesterol efflux facilitated by lipid-free apolipoprotein A1 (ApoA1) or other high-density lipoprotein (HDL) particles within the interstitial space. Extracellular cholesterol then is picked up and transported through the lymphatic vasculature before entering into bloodstream. There is increasing evidence supporting a role for enhanced macrophage cholesterol efflux and RCT in ameliorating atherosclerosis, and recent data suggest that these processes may serve as better diagnostic biomarkers than plasma HDL levels. Hence, it is important to better understand the processes governing ApoA1 and HDL influx into peripheral tissues from the bloodstream, modification and facilitation of cellular cholesterol removal within the interstitial space, and transport through the lymphatic vasculature route. New findings will complement therapeutic strategies for the treatment of atherosclerotic vascular disease.